2009
DOI: 10.2217/nnm.09.71
|View full text |Cite
|
Sign up to set email alerts
|

NanoART Synthesis, Characterization, Uptake, Release and Toxicology for Human Monocyte–Macrophage Drug Delivery

Abstract: Background Factors limiting the efficacy of conventional antiretroviral therapy for HIV-1 infection include treatment adherence, pharmacokinetics and penetration into viral sanctuaries. These affect the rate of viral mutation and drug resistance. In attempts to bypass such limitations, nanoparticles containing ritonavir, indinavir and efavirenz (described as nanoART) were manufactured to assess macrophage-based drug delivery. Methods NanoART were made by high-pressure homogenization of crystalline drug with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
175
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(186 citation statements)
references
References 48 publications
11
175
0
Order By: Relevance
“…The zeta potential was Ϫ28.9 mV, and the negative charge was contributed by P407. Scanning electron microscopy revealed smooth rod-like morphologies for the nano-ATV particles (data not shown) and confirmed the size measurements and distribution, which were consistent with our previous studies (9,10).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The zeta potential was Ϫ28.9 mV, and the negative charge was contributed by P407. Scanning electron microscopy revealed smooth rod-like morphologies for the nano-ATV particles (data not shown) and confirmed the size measurements and distribution, which were consistent with our previous studies (9,10).…”
Section: Resultssupporting
confidence: 91%
“…Drug retention in MDM was determined 24 h after treatment. In MDM treated with nanoATV, drug levels of 28.5 g/10 6 cells and 14.0 g/10 6 cells in the 70-and 30-g/ml treatment groups, respectively, were sustained over 24 h. Sustained release was expected for up to 15 days with nanoparticle treatment based on previous studies (6,10). Much less ATV was detected 24 h following treatment with native ATV.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…4,11,12 Prior works demonstrated that such nanoART could be carried in monocyte-macrophages and reach viral sanctuaries. [11][12][13][14][15] These studies also showed that size, shape, and charge of crystalline indinavir (IDV), ritonavir (RTV), atazanavir (ATV), and efavirenz (EFV) affect uptake, release, cytotoxicities, and antiretroviral responses.…”
Section: Introductionmentioning
confidence: 99%
“…26 Nano-ART can be taken up within minutes by circulating monocytes and released in tissues over a period of 2 weeks. [56][57][58][59][60] Theoretically, cell-based nano-ART would travel to sites of inflammation and release drug(s) slowly with limited tissue toxicities. Such a drug-delivery system can revolutionize HIV-1 therapeutics and can particularly target virus sequestration.…”
Section: Targeted Drug Delivery Of Antiretroviralsmentioning
confidence: 99%